1986
DOI: 10.1136/bmj.293.6545.471
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of angiotensin converting enzyme inhibition on renal function in patients with diabetic nephropathy.

Abstract: The effects of angiotensin converting enzyme inhibition with captopril were investigated in patients with diabetic nephropathy and hypertension. After nine days' treatment with captopril glomerular filtration rate was unchanged in 13 patients, whereas renal plasma flow had increased from 265 to 302 ml/min/173 ml body surface area (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
97
1
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(107 citation statements)
references
References 12 publications
5
97
1
4
Order By: Relevance
“…Hypertension is often associated with diabetic nephropathy [2], and effective antihypertensive treatment has proven to be effective in slowing the progression rate of nephropathy [3][4][5]. Recent studies in patients with diabetic nephropathy suggest that the use of angiotensin converting enzyme (ACE) inhibitors may possess specific advantages in decreasing proteinuria and slowing progression of nephropathy [6][7][8][9]. Nevertheless, whether such renal effects can be seen only with ACE inhibitors or whether ACE inhibitors have more beneficial renal effects as compared to other conventional antihypertensive drugs is uncertain.…”
mentioning
confidence: 99%
“…Hypertension is often associated with diabetic nephropathy [2], and effective antihypertensive treatment has proven to be effective in slowing the progression rate of nephropathy [3][4][5]. Recent studies in patients with diabetic nephropathy suggest that the use of angiotensin converting enzyme (ACE) inhibitors may possess specific advantages in decreasing proteinuria and slowing progression of nephropathy [6][7][8][9]. Nevertheless, whether such renal effects can be seen only with ACE inhibitors or whether ACE inhibitors have more beneficial renal effects as compared to other conventional antihypertensive drugs is uncertain.…”
mentioning
confidence: 99%
“…5,9 Several studies have linked increased renin angiotensin aldosterone system activity to enhanced renal Nox activity and ROS generation. 5,17 Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers slow progression of proteinuria in models of diabetes, and these effects may be, in part, independent of their effects on systemic BP, [17][18][19][20] because direct activation of Nox enzymes through the angiotensin II (AngII)/AT1 receptor (AT1R) pathway leads to oxidative stress. In vitro studies in both human and rodent cell lines have also shown that Nox family member expression and activity are regulated by disease-associated factors, including AngII, ET-1, TGF-b, high glucose, mechanical stretch, and PDGF (factors that are upregulated in the diabetic milieu).…”
mentioning
confidence: 99%
“…Inhibitors of angiotensin-con-verting enzyme (ACE) and angiotensin II receptor blockers are thought to be involved in the development of DN (Bjorck et al 1986;Whitty and Jackson 1988;Onozato et al 2002). We previously reported the frequent occurrence of nephropathy in diabetic patients with genotype D of the ACE gene (Mizuiri et al 1995(Mizuiri et al , 1997 and that, in the kidney from the D genotype population, the number of transcripts of the ACE gene is higher than in I genotype (Mizuiri et al 2001), suggesting that ACE activity contributes to the development of DN.…”
mentioning
confidence: 99%